APLIKASI PROGRAMA DINAMIS UNTUK OPTIMASI KEANDALAN SISTEM MPEG BOARD DAN POWER SUPPLY VCD PLAYER - Jemmy Loarens; Abdullah Shahab (Lembaga Penelitian dan Pengabdian kepada Masyarakat- Institut Teknologi Sepuluh Nopember, 2005)
VCD Player consists of 3 electrical parts, MPEG Board, Loader Module, and Power Supply. These parts comprise several components, which could be procured from different suppliers, at a variable reliability and costs. A study was carried out to determine a choice and an optimal combination of these components to satisfy the reliability of the system and available budget. Optimization was performed using Deterministic Dynamic Programming method. The characteristically non-linear equation of the objective function of this problem made the Dynamic Programming (DP) a reasonable alternative. By assigning stages, states, decision variables, and pay-off, which characterized the feature of DP model, related to the choice and the cost of the components, optimization of the problem, which was done by stages, could be done. In this study, two versions of optimization were done: to optimize the reliability of the system constrained by the budget available, and to optimize the cost subjected to a determined reliability of the system. The results showed that optimization of system reliability using DP resulted in optimal system reliability in a constrained budget. The method used is also proven able to obtain a reliability of the system hitherto required, even with a relatively lower budget.